Kompensationsstrategien älterer Kraftfahrer = Compensation strategies of elderly drivers - Germann, Susanne; Schaul, Martine; Strohbeck-Kühner, Peter (Rechtsmedizin, 2016)
BackgroundThe increasing proportion of elderly people in populations means that an increasing number of drivers with reduced executive functions due to age-related reasons have to be expected. Thus, an important question is how elderly drivers compensate for deficits in executive functioning and how these drivers can be identified.ObjectiveThis article is based on the hierarchical model of Michon and focuses on the analyses of characteristic behavior, attitudes and personality traits of elderly drivers who try to enhance their driving abilities based on individual compensation and coping strategies, compared to drivers who do not.Material and methodsA sample of 42 drivers conducted driving exercises, as well as psychometric tests and a semi-structured interview, in order to obtain as broad a database as possible.ResultsThe results of this study provide evidence that age per se is not a good predictor for fitness to drive.ConclusionThe best predictor for the use of compensation strategies is the ability of elderly drivers to perceive and identify subjective mental stress and limitations of driving skills.
Gesehen am 07.12.2018